Antimicrobial Chemotherapy has a Linear Relationship to the Proportion of Gram-Negative Isolates from Pediatric Burn Wounds - Welk, Alexa; Herrnberger, Myriam; Engel, Veronika; Dennebaum, Martin; von Sochaczewski, Christina Oetzmann; Gehring, Stephan (Klinische Pädiatrie, 2018)
Wound infection in burns is a relevant cause of morbidity and mortality in children. We aimed to determine the relationship between antibacterial chemotherapy and Gram-negative burn wound colonization and infection. All children admitted to the pediatric intensive care unit for burn trauma from June 1, 2005 to January 31, 2013 were included. We obtained 141 wound samples, of which 88 (65.7%) showed growth of Gram-positive bacteria. Treatment with antimicrobial chemotherapy was necessary in 23 (31.1%) patients. The proportion of Gram-negative isolates seems to increase linear from 12.5% (95% confidence interval (CI): 4.4%–28.7%) without antibacterial chemotherapy to 36.8% (95% CI: 25.5%–49.6%) with one to 48.9% (95% CI: 35.3%–62.8%) with 2 antimicrobial agents. The Odds ratio for a Gram-negative isolate, in comparison to patients without antibacterial chemotherapy, increased from 4.083 (95% CI: 1.140–15.961) for one administered substance to 6.708 (95% CI: 1.832–26.786) if 2 or more were used. Conclusion We found that antibacterial chemotherapy seems to facilitate burn wound colonization and results in an increased number of gram-negative isolates from children with burn wounds.
Keywords: burn; child infection; antimicrobial chemotherapy